Analisis Persediaan Bahan Baku Botol Insektisida Kemasan 1 Liter dengan Metode Material Requirement Planning (MRP) untuk Mengetahui Tingkat Kestabilan Bahan Baku - Arinda Soraya Putri; Bagus Imron Rosydi (Universitas Serang Raya, 2020)
PT. Agricon mostly produces 1L package (bottle) pesticides named Spontan insecticide. This study was conducted to analyze and determine the stock inventory of 1L bottles for determining an effective ordering schedule based on the calculation of safety stock and reorder points to optimize planning and inventory. Material Requirement Planning (MRP) method used to determine the effective scheduling of 1L bottle products. Material Requirement Planning is one method used to determine scheduling with advantages such as reducing inventory, reducing set up costs, and reducing idle time. The proposed order scheme for ordering 1L insecticide packaging bottle improve the company on reducing the frequency for ordering bottles from 7 times to 5 times and inventory is more stable and close to demand quantity